The Safety of Propofol Versus Sevoflurane for General Anesthesia in Children: A Meta-Analysis of Randomized Controlled Trials - Ying Zhao; Feng Qin; Feng Qin; Yuhang Liu; Yanping Dai; Xiaobo Cen (Frontiers in Surgery, 2022)
BackgroundPropofol and sevoflurane are the most used anesthetics for pediatric surgery. Emergence agitation, postoperative nausea and vomiting and postoperative pain are the primary adverse effect of these general anesthetics. Many clinical studies had compared the safety of propofol and sevoflurane in pediatric surgery, but the results were controversial.ObjectivesTo evaluate the evidence surrounding the safety of propofol versus sevoflurane for general anesthesia in children.MethodsDatabases including PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure, Wanfang Data and Vip Data were searched to collect relevant articles. Trials were strictly selected according to previously defined inclusion and exclusion criteria. RevMan 5.3 software was used for meta-analyses.ResultsTwenty randomized controlled trials recruiting 1,550 children for general anesthesia were included, with overall low-moderate methodological quality. There was evidence that compared with sevoflurane anesthesia, propofol anesthesia significantly decreased the incidence of emergence agitation (OR = 4.99, 95% CI, 3.67–6.80; P < 0.00001), postoperative nausea and vomiting (OR = 1.91, 95% CI, 1.27–2.87; P  =  0.002) and postoperative pain (OR = 1.72, 95% CI, 1.11–2.64; P = 0.01) in children. However, patients who received sevoflurane tended to have shorter times to eye opening (MD = −2.58, 95% CI, −2.97– −2.19; P < 0.00001) and times to extubation (MD = −1.42, 95% CI, −1.81– −1.02; P < 0.00001).ConclusionsThis review reveals that the children who received propofol anesthesia had the lower risks of emergence agitation, postoperative nausea and vomiting and postoperative pain when compared with sevoflurane anesthesia. But the children who received sevoflurane recovered slightly faster than those received propofol. Considering the limitations of the included studies, better methodological quality and large controlled trials are expected to further quantify the safety of propofol and sevoflurane for general anesthesia in children.